Liver-related long-term outcomes of alpha-glucosidase inhibitors in patients with diabetes and liver cirrhosis - Yen, Fu-Shun; Hou, Ming-Chih; Wei, James Cheng-Chung; Shih, Ying-Hsiu; Hsu, Chung Y.; Hsu, Chih-Cheng; Hwu, Chii-Min (Frontiers in Pharmacology, 2022)
Background: Adequate management of diabetes in patients with liver cirrhosis can be challenging. We conducted this study to investigate the liver-related long term outcomes of alpha-glucosidase inhibitors (AGIs) in patients with diabetes and cirrhosis. Methods: From National Health Insurance Research Database (NHIRD) in Taiwan, we recruited propensity-score matched alpha-glucosidase inhibitor users and non-users from a cohort of type 2 diabetes mellitus (T2DM) with compensated liver cirrhosis between 1 January 2000, and 31 December 2017, and followed them until 31 December 2018. Cox proportional hazards models with robust sandwich standard error estimates were used to assess the risk of main outcomes for alpha-glucosidase inhibitor users versus non-users. Results: The incidence rates of mortality during follow-up were 65.56 vs. 96.06 per 1,000 patient-years for alpha-glucosidase inhibitor users and non-users, respectively. The multivariable-adjusted model shows that alpha-glucosidase inhibitor users had significantly lower risks of all-cause mortality (aHR 0.63, 95% CI 0.56–0.71), hepatocellular carcinoma (aHR 0.55, 95% CI 0.46–0.67), decompensated cirrhosis (aHR 0.74 95% CI 0.63–0.87), hepatic encephalopathy (aHR 0.72, 95% CI 0.60–0.87), and hepatic failure (aHR 0.74, 95% CI 0.62–0.88) than alpha-glucosidase inhibitor non-users. Patients who received alpha-glucosidase inhibitors for a cumulative duration of more than 364 days had significantly lower risks of these outcomes than non-users. Conclusion: Alpha-glucosidase inhibitor use was associated with a lower risk of mortality, hepatocellular carcinoma, decompensated cirrhosis, and hepatic failure in patients with diabetes and compensated cirrhosis. alpha-glucosidase inhibitors may be useful for the management of diabetes in patients with compensated liver cirrhosis. Large-scale prospective studies are required to verify our results.